A Qualitative Study of Service Provision for Alcohol Related Health Issues in Mid to Later Life. - Catherine Haighton; Graeme Wilson; Jonathan Ling; Karen McCabe; Ann Crosland; Eileen Kaner (PLoS ONE)
Aims Epidemiological surveys over the last 20 years show a steady increase in the amount of alcohol consumed by older age groups. Physiological changes and an increased likelihood of health problems and medication use make older people more likely than younger age groups to suffer negative consequences of alcohol consumption, often at lower levels. However, health services targeting excessive drinking tend to be aimed at younger age groups. The aim of this study was to gain an in-depth understanding of experiences of, and attitudes towards, support for alcohol related health issues in people aged 50 and over. Methods Qualitative interviews (n = 24, 12 male/12 female, ages 51-90 years) and focus groups (n = 27, 6 male/21 female, ages 50-95 years) were carried out with a purposive sample of participants who consumed alcohol or had been dependent. Findings Participants' alcohol misuse was often covert, isolated and carefully regulated. Participants tended to look first to their General Practitioner for help with alcohol. Detoxification courses had been found effective for dependent participants but only in the short term; rehabilitation facilities were appreciated but seen as difficult to access. Activities, informal groups and drop-in centres were endorsed. It was seen as difficult to secure treatment for alcohol and mental health problems together. Barriers to seeking help included functioning at a high level, concern about losing positive aspects of drinking, perceived stigma, service orientation to younger people, and fatalistic attitudes to help-seeking. Facilitators included concern about risk of fatal illness or pressure from significant people. Conclusion Primary care professionals need training on improving the detection and treatment of alcohol problems among older people. There is also a compelling need to ensure that aftercare is in place to prevent relapse. Strong preferences were expressed for support to be provided by those who had experienced alcohol problems themselves.